Determinant Associated with Anemia in Adolescent Girls: A School-Based Cross-Sectional Study - Merita Yumna Nisrina; Sinaga, Evi Susanti (RRZ Scientific Publishing, 2025)
In Indonesia, anemia remains a pressing public health problem among adolescent girls, with a prevalence rate of 32% based on the Basic Health Research (Riskesdas) 2018. This highlights anemia as an ongoing issue that requires continuous attention. Adolescent girls are particularly vulnerable because iron needs increase during growth, and blood loss occurs regularly through menstruation. Inadequate intake of nutritious foods, poor adherence to iron supplementation (TTD), limited knowledge, and economic barriers may further contribute to this problem. This cross-sectional study investigated the determinants of anemia among adolescent girls attending a public vocational high school in Tebet, Jakarta, Indonesia. A total of 221 Grade 11 students were included through total sampling. Anemia status (Hb < 12 g/dL) was obtained from puskesmas screening, while data on knowledge, nutritional status, menstrual pattern, maternal education, socioeconomic status, and iron supplement (TTD) intake were collected via a structured questionnaire. Chi-square analysis revealed significant associations between anemia and knowledge level, menstrual pattern, nutritional status, adherence to TTD, maternal education level, and socioeconomic status (p < 0.05). The findings emphasize the need for strengthened school-based anemia prevention through nutrition education, routine Hb screening, and parent-involved adherence monitoring, particularly among low-income students. The findings indicate the need for schools and primary health centers (puskesmas) to strengthen education on anemia and adolescent nutrition, implement routine screening (nutritional status and menstrual pattern), and improve adherence to TTD through regular mentoring that involves parents, particularly mothers, and targeted support for students from low-income households.